Readiness for Risk among Higher Education Students in the Context of Social Changes - Ihor Hoian; Mariia Myshchyshyn; Andrii Petraniuk; Serhii Ilchuk (Insight: the psychological dimensions of society, 2025)
The aim is a theoretical-empirical study of the phenomenon of readiness for risk among higher education students in the context of relevant social changes. Methods. The sample consisted of students from three levels of higher education: Bachelor’s, Master’s, and prospective Ph.D. candidates, who were studying at universities in Ukraine, totaling 114 individuals (M = 21.04; SD = ±3.75). The social changes affecting students and their higher education institutions validly reproduced the key conditions of the research. The methodologies used met the main criteria: validity, reliability, and representativeness, and were adapted and/or tested on a Ukrainian sample. The parameters studied were assessed using the following psychodiagnostic instruments: “Diagnosis of Readiness for Risk” (RSK) (Schubert, 1964), “Test-Questionnaire of Qualitative Components of Risk Tendency” (TRT) (Sannikova & Bykova, 2008), and “Personal Readiness for Change Questionnaire” (PRCQ) (Rollnick et al., 1992). Results. A confirmatory research strategy was employed to compare the studied variables. A matrix of psychological correlates was constructed. It was established that the predominance of direct relationships provides grounds to assert that with an increase in readiness for risk, there is also an increase in readiness for personal changes, and correspondingly, with an increase in readiness for personal changes, the willingness to take risks also increases. It was clarified and justified that nine inverse relationships between risk parameters and creativity, adaptability, and tolerance for ambiguity indicate an inverse pattern. It was explained that these internalized properties of creativity, optimism, adaptability, and tolerance for ambiguity in respondents with low readiness to take risks are reflected in coping behavior strategies and can be realized through the operation of defense mechanisms. Discussion and Conclusions. It was substantiated that the readiness for risk among respondents in the context of social changes is a stable, multifaceted, and hierarchical property of personality, which can determine behavior strategies under uncertainty, based on analyzing the current situation and personal capabilities. It was explained that the recorded significant differences indicate personality traits that have become pronounced in current situations of social change. It was noted that these traits are important contours of the psychological profile of the higher education seeker in the context of relevant situations of social change. The obtained correlations and significant differences represent scientific value within the context of the research subject.